2008
DOI: 10.1016/j.jpsychires.2007.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Self-mutilative behaviors in male veterans with posttraumatic stress disorder

Abstract: Self-mutilative behaviors (SMB) were examined in a sample of male veterans with posttraumatic stress disorder (PTSD). The primary objective was to determine the prevalence of SMB and any physical, cognitive, or affective antecedents and correlates for these behaviors. Participants included 509 male veterans with PTSD and levels of PTSD, depression, alcohol use, hostility, and impulsivity were evaluated to determine if these variables were related to SMB. Antecedents and sequelae of SMB were also examined to ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 57 publications
(44 reference statements)
3
53
0
Order By: Relevance
“…There were no differences between individuals who engaged in NSSI and individuals who did not engage in NSSI, however, on lab-based measures of impulsivity (Glenn & Klonsky, 2010;Janis & Nock, 2009;McCloskey et al, 2012). Moreover, the link between impulsivity and NSSI found for self-report measures was eliminated in some studies when researchers controlled for other risk factors for NSSI Carli et al, 2010;Evren et al, 2012;Rodav et al, 2014;Sacks et al, 2008). Longitudinal research on the link between impulsivity and NSSI also was limited and findings were mixed (Chapman et al, 2009;Glenn & Klonsky, 2011;.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There were no differences between individuals who engaged in NSSI and individuals who did not engage in NSSI, however, on lab-based measures of impulsivity (Glenn & Klonsky, 2010;Janis & Nock, 2009;McCloskey et al, 2012). Moreover, the link between impulsivity and NSSI found for self-report measures was eliminated in some studies when researchers controlled for other risk factors for NSSI Carli et al, 2010;Evren et al, 2012;Rodav et al, 2014;Sacks et al, 2008). Longitudinal research on the link between impulsivity and NSSI also was limited and findings were mixed (Chapman et al, 2009;Glenn & Klonsky, 2011;.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note, however, that participants in these studies were overwhelmingly identified as Caucasian. There were only a few studies that included an examination of the link between impulsivity and NSSI among minority samples (e.g., African, Bornovalova et al, 2011;Lynam et al, 2011;Sacks et al, 2008); thus, the results of the review may not be generalizable to more diverse racial/ethnic populations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among a clinical sample of over 500 veteran men who met criteria for PTSD, Sacks and colleagues found over half of the respondents indicated self-mutilating behavior in the last two weeks, and those who reported self-harm had significantly worse mental health profiles, including depression and more severe PTSD. 30 It is unclear whether there are differences among deliberate self-harm among nonclinical samples of service members/veterans compared with those without military service experience. Since self-harm behaviors are prevalent among young adults, 17,20,21 college attending samples may constitute a particularly useful population in which to investigate differences in self-harm behaviors by military experience.…”
Section: Introductionmentioning
confidence: 99%